PENGARUH PENATAUSAHAAN ASET TETAP, EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL, DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN BARANG MILIK DAERAH DENGAN SISTEM INFORMASI MANAJEMEN ASET JEPARA (SIMANJA) SEBAGAI VARIABEL MODERASI - Sindy, Helmalia; Handayani, Bestari Dwi (Jurnal Akuntansi dan Governance Andalas, 2025)
This study aims to examine the effect of fixed asset administration, the effect of fixed asset administration, effectiveness of internal control system, and human resource competence on the quality of regional asset report with Jepara Asset Management Information System (SIMANJA) as a moderating variable. The population in this study were all Regional Apparatus Organizations (OPD) in Jepara Regency, namely 42 Regional Apparatus Organizations (OPD). Sampling was carried out using purposive sampling method by distributing questionnaires to 46 respondents. The data analysis technique used multiple linear analysis techniques and Moderated Regression Analysis (MRA) with the help of the IBM SPSS Statistic version 27 program. The results of this study indicate that fixed asset management and human resource competence have a positive effect on the quality of regional asset reports. The effectiveness of the internal control system does not affect the quality of regional asset reports. The Jepara Asset Management Information System (SIMANJA) strengthens the relationship between fixed asset management and human resource competence on the quality of regional asset reports. The Jepara Asset Management Information System (SIMANJA) does not moderate the relationship between the effectiveness of the internal control system on the quality of regional asset reports. This study specifically discusses the quality of the Regional Asset Report (BMD), which is an important part of fixed asset management, but has rarely been the main focus in previous studies. This study also presents novelty by making the Asset Management Information System (SIMANJA) a moderating variable.